THE INFLUENCE OF BRAND LOVE ON BRAND LOYALTY ON H&M GLOBAL FASHION BRANDS IN JAKARTA - Febri Rakhmawati Arsj (Faculty of Economic and Business, University of Pasundan, 2022)
This study was conducted to observe and test brand love against brand loyalty at the global fashion brand H & M in Jakarta. This research is descriptive quantitative research by distributing questionnaires through the google form platform which is distributed to 115 respondents who live in the city of Jakarta and have made purchases at least twice. The results of this study were analyzed through validity test, reliability test and T test using SPSS as an analytical tool. This study reveals that the brand love variable has a significant positive effect on brand loyalty as seen by the t-count value of 4.431 > 1.984 and a significant value of 0.000 < 0.05. The higher the brand love will be able to increase the intensity of consumers loyal to the brand. the contribution made, namely, H & M is expected to be able to maintain and strengthen brand love (love of brands). This will create intensity that consumers will make regular repeat purchases and will promote them to a wide audience.